Slovenian version of the European Deprivation Index at municipal level - Zadnik, Vesna (Zdravstveno varstvo, 2018)
Introduction: Ecological deprivation indices belong to essential instruments for monitoring and understanding health inequalities. Our aim was to develop the SI-EDI, a newly derived European Deprivation Index for Slovenia. We intend to provide researchers and policy-makers in our country with a relevant tool for measuring and reducing the socioeconomic inequalities in health, and even at a broader level. Methods: Data from the European survey on Income and Living Conditions and Slovenian national census for the year 2011 were used in the SI-EDI construction. The concept of relative deprivation was used where deprivation refers to unmet need(s), which is caused by lack of all kinds of resources, not only material. The SI-EDI was constructed for 210 Slovenian municipalities. Its geographical distribution was compared to the distribution of two existing deprivation scores previously applied in health inequality research in Slovenia. Results: There were 36% of adults recognized as deprived in Slovenia in 2011. SI-EDI was calculated using 10 census variables that were associated with individual deprivation. A clear east-to-west gradient was detected with the most deprived municipalities in the eastern part of the country. The two existing deprivation scores correlate significantly with the SI-EDI. Conclusions: A new deprivation index, the SI-EDI, is grounded on the internationally established scientific concept, can be replicated over time and, crucially, provides an account of the socioeconomic and cultural particularities of the Slovenian population. The SI-EDI could be used by the stakeholders and the governmental and nongovernmental sectors in Slovenia, with the goal of better understanding health inequalities in Slovenia.
Keywords: deprivation index; European Deprivation Index - Slovenian version; health inequalities; kazalnik primanjkljaja; neenakosti v zdravju; slovenska verzija evropskega kazalnika primanjkljaja; socialno-ekonomske determinante; socioeconomic determinants